Rogeaulito: A World Energy Scenario Modeling Tool for Transparent Energy System Thinking - Benichou, Léo; Mayr, Sebastian (Frontiers in Energy Research, 2014)
Rogeaulito is a world energy model for scenario building developed by the European think tank The Shift Project. It’s a tool to explore world energy choices from a very long-term and systematic perspective. As a key feature and novelty it computes energy supply and demand independently from each other revealing potentially missing energy supply by 2100. It is further simple to use, didactic and open source. As such, it targets a broad user group and advocates for reproducibility and transparency in scenario modeling as well as model-based learning. Rogeaulito applies an engineering approach using disaggregated data in a spreadsheet model.